SME competitiveness and internationalization - internationalization of B5 plus international entry mode selection LR - Brito, Carolina Silva Cacho Borges de (2021)
This work project aims to build an internationalization strategy for B5, a tourism firm with multiple services and brands. The strategy for selecting international markets was performed using analytical approaches based on secondary data. The chosen target market was France, with Paris being the city chosen for a wholly-owned subsidiary. Finally, a marketing strategy and financial forecast were used to establish the expansion strategy. According to the financial forecast, the business is predicted to continue growing after 2025. Also, a literature reviewon international entry mode selection was undertaken, as well as an in-depth analysis of France.